Life Outcomes Influenced by War-Related Experiences During the Gulf Crisis - Hadi, Fawzyiah (2013)
This study examined the life outcomes of children exposed to the Gulf crisis in 1990 – 1991. We expected war-trauma exposure and psychological distress symptoms to predict poorer educational and occupational outcomes. Participants were 151 Kuwaiti citizens who were assessed during childhood (in 1993; M age = 10.6 years), and who were reassessed 10 years later in young adulthood (in 2003; M age = 21.2 years). Participants completed measures of intelligence, war-trauma exposure, posttraumatic stress symptoms, anxiety symptoms, depressive symptoms, intervening life events, and life outcomes. Results indicated that war-trauma exposure negatively impacted children’s educational and occupational outcomes as young adults. Boys with higher levels of war-trauma exposure were less likely to attend University. Posttraumatic stress and anxiety symptoms also predicted poorer educational and occupational outcomes. However, this relationship was not significant when we accounted for children’s intelligence. Depressive symptoms were not predictive of children’s educational or occupational outcomes. Results suggest that war-trauma exposure may have life altering effects on children. Tailored, early interventions are needed for children exposed to war traumas.